Group 8 Transition Metal Complexes of the Tripodal Triphosphino Ligands PhSi(CH2PR2)3 (R = Ph, iPr). Issue 36 (19th November 2013) - Neumeyer, Felix; Lipschutz, Michael I.; Tilley, T. Don
Abstract: A series of group 8 transition metal complexes of new tridentate phosphine ligands with Fe, Ru, and Os were prepared. The new complexes were characterized by multinuclear NMR spectroscopy and X‐ray crystallography. Abstract : Complexes of iron, ruthenium, and osmium with the neutral tridentate tripodal phosphine ligands PhSi(CH2 PPh2 )3 and PhSi(CH2 P i Pr2 )3 show tetrahedral coordination for iron and form cationic dimeric octahedral complexes with the heavier homologues ruthenium and osmium.